Pengaruh Kompensasi Terhadap Kepuasan Kerja pada Karyawan yang dialihdayakan (Studi kasus pada PT. Bakrie Telecom, Tbk) - Fortunisa, Ananda; Febrina, Dina (Business and Management Review, 2011)
Employee satisfaction is important for a company in creating employment viability, regardless of the type of work. One effort to create high satisfaction of employment is to provide adequate compensation for employees. Lately companies that use outsourced workers or employees who are outsourcing more and more prevalent and it is a challenge for corporate users of outsourcing employees to realize the employee job satisfaction, one way is to provide appropriate compensation. Their are two forms of compensation, direct compensations and indirect compensations, direct compensations are namely salary, incentive and bonus compensations while indirect compensations consists of health support, safety support, holiday allowances, and employee welfare facilities. The purpose of this study was to determine the implementation of compensation given to outsourced employees at PT. Bakrie Telecom, to find out the level of employment satisfaction of outsourced employees, to know the influence of compensation towards employment satisfaction, and the types of employee compensation that have a significant influence on employment satisfaction. This research is uses a descriptive analysis, the variables used in this research are; direct compensation (X1), indirect compensation (X2) and empoyment satisfaction (Y) As for the samples taken for this reasearch consist of 50 respondents. The sampling method used for this reasearch is probability sampling. Based on the calculation the hypothesis test showed that the partial direct compensation variable (X1) adversely affect the Employee Satisfaction variable (Y) and indirect compensation variable (X2 ) has a positive effect on Employment satisfaction variable (Y). The results of the analysis uses a multiple linear Regression method where the R-square obtained is at 0.548. While the variable that has the most significant influence is Indirect Compensation variable, with a value of B (beta) at 0.582. Keywords: Direct Compensation, Indirect Compensation, Job satisfaction